Ocena działań opozycji parlamentarnej z punktu widzenia polityki prawa. Analiza zjawiska kontrprojektów ustaw - Zyzik, Radosław (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The parliamentary opposition is regarded as both positive and necessary for the existence of a democratic political system. Opposition, in addition to legislative and control purposes in relation to the ruling party, has its primary objective, which is to win the next elections. So the question arises of the means of undermining the endorsement for the ruling party, of which at least some are related to the politicization of legislative procedures. The article analyzes the phenomenon of the legislative counter-proposals, which are an example of the politicization of legislation, understood as a breach of the rules and good practices of legislation in order to achieve political goals. The analysis will be carried out from a perspective of scientific legal policy, the discipline belonging to legal sciences involved in the establishment and development of conditions for the efficient creation and application of the law.
The assessment of activity of the parliamentary opposition from the perspective of legal policy. An analysis of the phenomenon of the legislative counter-proposals
Keywords: legal policy; opposition; legislative counter-proposals